YouTube Itak: a description of Ainu-related videos - Xanat Vargas Meza; R. Shizuko Hayashi-Simpliciano; Takumi Yokoyama; Chieko Nishimura; Ryohei Nishida; Yoichi Ochiai (Humanities & Social Sciences Communications, 2023)
Abstract The Ainu are an Indigenous group currently living primarily in Japan. Following the cultural revitalisation of laws and social movements and the appropriation of new technologies, Ainu communities are increasingly using social media to disseminate their culture. However, research on the Ainu people has rarely discussed their communication strategies in current media. In this study, a total of 428 Ainu-related videos uploaded on YouTube were analysed. Basic information about the videos was obtained through the YouTube application programming interface and additional information was acquired by watching them. The videos were categorised into three groups: those produced only by Ainu people, with Ainu people, or without Ainu collaborators. Statistical and qualitative differences between release and upload dates, keywords, categories, conceptualisers, producers, presenters, YouTube metrics, tags, and video descriptions were used to uncover the different types of content created and/or endorsed by Ainu people and the communication strategies used by them and their allies. The combination of quantitative and qualitative methods based on Indigenous communication approaches adopted in this study proved to be useful in understanding Indigenous media in online contexts.